Efektifitas Terapi Aroma Lemon Terhadap Penurunan Skala Nyeri Pada Pasien Post Laparatomi - Fadhla - Purwandari; Siti Rahmalia HD; Febriana - Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to identify the effectivitas of lemon aromatherapy to decrease pain scale among patients post laparatomy. This study was quasy experiment design by used pre test and post test. The population for this study was patients post laparatomy in Awal Bros and Syafira Hospital Pekanbaru. Systematic purposive sampling was used to select 30 sample. The study was conducted during 15-23 january 2014. The method was observation by used numeric scale of pain. The intervention provided to experiment group as long as 10 minute to inhale of lemon aromatherapy. The data collection was analyzed by t dependent and t independent. The demographic of each group was mayority senior high school (60%) and women (70%). The result of study showed that there was very significant of lemon aromatherapy to decrease of pain scale among patients post laparotomy (p=0,000). According to the result of study, the researcher recommended for health provider to aplicate the alternative therapy to reduce pain by using non farmachology. Keywords : lemon aromatherapy,pain,  post-laparotomy